A facile self-assembly strategy towards naphthalene diimide/graphene hybrids as high performance organic cathodes for lithium-ion batteries. Issue 17 (2nd February 2016) - Chen, Miao; Yang, Chongqing; Xu, Zhixiao; Tang, Yanping; Jiang, Jianzhong; Liu, Ping; Su, Yuezeng; Wu, Dongqing
Abstract : A hybrid of naphthalene diimide and reduced graphene oxide (NDI–RGO) has been constructed by a facile self-assembly strategy. As the cathode material in lithium ion batteries, NDI–RGO manifests a capacity of 170 mA h g −1 at 25 mA g −1 for 260 cycles. Abstract : A two-dimensional hybrid of naphthalene diimide and reduced graphene oxide (NDI–RGO) has been constructed by a facile self-assembly strategy. In the resulting hybrid, the non-covalent interactions between NDI and RGO enable the uniform distribution of NDI on the surface of RGO. As the cathode material in lithium ion batteries, NDI–RGO shows excellent revisable capacity and rate capability.